Structural investigations of Yuli Geothermal field in Nigeria using gravity and magnetic data-set - Mukaila Abdullahi; Yusufu Abubakar Sanusi; Ibrahim Nihyel Tashiwa (Results in Earth Sciences)
Yuli is part of the Yankari area of the Upper Benue trough. Four important locations of warm spring are found in the area. These are namely, the Gwama Warm Spring (GWS), the Wikki Warm Spring (WWS), the Mawulgo Warm Spring (MWS) and the Tongan-Maliki Warm Spring (TWS). Identification, mapping and interpretation of geological structures/features buried within the crust or exposed on the surface are important steps if not necessary in understanding the general geo-tectono-magmatism of a region. Gravity and magnetic data are employed for the interpretation of identified geologic/tectonic features/structures in the area of study. Different filtering techniques are employed. Total Horizontal Derivative of Tilt Derivative (HD_TDR), Horizontal Gradient (HG) and Generalized Derivative Operation (GDO) filters are found better option for the interpretation of the gravity data whereas for the magnetic data, First Vertical Derivative (FVD) and the Analytic Signal (AS) are found the better filters for the magnetic anomalies of the region. The study found a close connects between the normal faults in the region with the magmatic plugs and as well with the warm springs in the area. Depths to anomalous sources are recorded between 0.5 km and 4.6 km in the study area. The depth results are found from 3D Euler deconvolution inversion method.